Movement Abnormalities Predict Transitioning to Psychosis in Individuals at Clinical High Risk for Psychosis - Callaway, Dallas A. (Schizophr Res, 2014)
Improving upon the predictive validity of determining the transition from high risk to actual psychosis is a primary aim of early intervention research. Previous research has suggested that premorbid spontaneous dyskinesias may be one possible predictor. In this study, dyskinetic movements were assessed with the Abnormal Involuntary Movement Scale (AIMS) at baseline of a longitudinal study of 148 individuals at clinical high risk (CHR) of developing psychosis. Twenty-eight individuals transitioned to a psychotic disorder over the course of the study. Group comparisons between transitioned and non-transitioned individuals indicated that, relative to those that were not observed to transition, participants that developed a psychotic disorder exhibited greater spontaneous dyskinesias at baseline. Moreover, increased dyskinetic movements at baseline resulted in a more than two-fold increase in odds of developing a psychosis for each point increase in AIMS scale score. These findings suggest that individuals with greater premorbid dyskinetic movements may comprise a subset of CHR individuals at inordinate risk to decompensate into psychosis. Future work should employ assessments of spontaneous dyskinesias by instrumentation (e.g., electromyography) and look to ascertain whether specific dyskinesias (e.g., dystonia) or dyskinesias of specific body regions are associated with transitioning to psychosis.